Sociable weaver nests as a resource to local animal communities - Lowney, Anthony (Department of Biological Sciences, 2022)
Animal space use in a landscape generally depends on resources. Facilitation by other species may impact resource availability that can positively influence local species diversity and community structure. Species that significantly change resource availability are often termed ecosystem engineers. The challenge here, is not only to document engineers that disproportionately influence ecosystems but also to determine their consequences to communities. I aim to understand the importance of a potential ecological engineer in a desert ecosystem to animal species diversity and community structure. I investigate how the role of this engineer may change with environmental harshness, and further examine specific associations and interactions with the host engineer. Sociable weavers (Philetairus socius) are a colonial passerine endemic to the semi-arid and arid Kalahari in the western parts of southern Africa. This species builds massive colonies that appear to form a focal point for the animal community in this system, and some species are known to show strict or strong associations with the colonies. Weaver colonies appear to be a resource to other animals in the environment, with food and nutrients clumped at colonies, and even thermal benefits available to occupants (a potentially crucial resource in arid environments). Nevertheless, the full importance of nest colonies to the surrounding animal community is still unknown. The main aims of this thesis were to determine the importance of Sociable weaver colonies to the surrounding animal communities and how this importance may change as environment harshness changes. To understand this, I investigate the use of colonies by multiple taxa (mammals, birds, reptiles and invertebrates) across seasonal and spatial aridity gradients. An additional aim is to describe the nature of the interactions between Sociable weavers and their associates. Therefore, determining how multiple species can access the colony resources at the same time and further, understand how these associates may impact the weavers. Here, I consider the interactions between Sociable weavers, Kalahari tree skinks (Trachylepis spilogaster), African pygmy falcons (Polihierax semitorquatus) and snakes. These species have all been shown to associate with weaver colonies and may impact weavers and each other in different ways. I show that Sociable weaver colonies create localised biodiversity hot-spots. These strong associations of multiple taxonomic groups which characterises their entire range and suggests a high importance of weaver colonies for the whole surrounding animal community. Although no variation was observed across a seasonal gradient, colony trees were associated with a greater abundance of animals at sites with lower rainfall, whereas sites with higher rainfall had a more evenly distributed abundance of animals between colony and non-colony trees. Additionally, I set out to describe the nature of the interactions between Sociable weavers and their recognised close associates. Through a series of observational and experimental studies I demonstrate that Kalahari tree skinks can eavesdrop on weaver alarm calls, this likely permits them to manage their predation risk and facilitate their coexistence with a predator, the pygmy falcon, at weaver colonies. The ability to eavesdrop also allows skinks to access riskier foraging habitat, thus, expanding their realised niche. Furthermore, pygmy falcon's defensive behaviour appears to deter predatory snakes from accessing a given colony. However, weaver reproductive output did not improve at falcon hosting colonies, suggesting falcon protection was offset by their predation of weaver chicks. Falcons saw an increase in nest predation when weavers were breeding, due to an increase in snake activity at colonies. When weavers were not breeding, falcons were more likely to fail, because of reasons other than predation (lack of provisioning, abandonment). This all demonstrates that weavers are clear-cut obligate ecosystem engineers, and one that can reduce stress that may allow species to persist in an environment that is predicted to become more harsh, due to global climate change. Furthermore, interactions at colonies demonstrate costs and benefits for weavers and their close associates, suggesting that a complicated ecological web of interactions allow these species to coexist.